Saproxylic beetles in artificially created high stumps of spruce and birch three years after cutting - Seedre, Meelis (2005)
According to the FSC and PEFC certification standards in Sweden, high stumps should be created during thinning and regeneration felling to reduce the negative effect of intensive forestmanagement on biodiversity, especially for the ca. 1000 species of wood dependent (saproxylic) beetles. To study the importance of high stumps for saproxylic beetles the fauna of 120 three-year old mechanically created high stumps of Norway spruce and Silver birch were sampled in the provinces of Halland, Kronoberg and Kalmar in Southern Sweden. Using bark peeling and sieving, 4179 individuals of saproxylic beetles were found, belonging to 66 species. Nine of the species were on the Swedish red-list. Of all caught beetle species the most common were Crypturgus pusillus, Phloeocharis subtilissima and Crypturgus hispidulus. The number of species was significantly different between spruce and birch high stumps, on average spruce stumps hosted 4.6 saproxylic species and birch stumps 5.5. Also the beetle assemblage on spruce and birch were different, implying that high stumps of both deciduous and coniferous species should be left, if possible. Other ecological variables like presumed diversity 'rich-poor' landscapes, geographical location and stump diameter (within the range of 20-58 cm and 21-40 cm for spruce and birch stumps, respectively) did not affect the species richness on stumps. Nevertheless, the 66 found species show the biological value of making high stumps. Furthermore, the occurrence of nine red-listed species indicates that high stumps are not only important for trivial species but contribute also to protection of threatened beetles. I conclude that mechanically created high stumps are important and valuable habitat supplement for saproxylic fauna.